Crush Response of Stacked Square Toroidal Tubes with A Central Tube / Naziratie Assrinie Assan ...[et al.] - Assan, Naziratie Assrinie; Ab. Ghani, Amir Radzi; Ramly, Ramzyzan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
An extensive study was carried out to determine the impact response of various impact attenuator designs. This study was important in order to develop and improve the energy absorption system and crashworthiness of impact attenuators. In the event of collision, vehicles are subjected to very high initial force. This phenomenon contributes severity of human injuries and damage to protected goods. New configuration in the form square of stacked toroidal tubes with a central tube was proposed. The aim of this study was to determine the performances and the characteristics of energy absorption of design configuration when subjected to axial static and impact loading. Finite element analyses were carried out using ABAQUS software. Aluminium Alloy AA6063-T5 of square tube was cut and welded into specific configuration for experiment purpose. The simulation results were verified by experiment before embarking into the simulation study. Results showed that the stacked toroidal tube had commendable impact energy absorbing capability. Stacked toroidal tube showed improvement in energy absorption and studied well as discussed in objectives.